Environmental monitoring system for the control of environmental conditions of aquaculture farms in the Peruvian jungle based on the internet of things - Lino Villaran, Adrian Ernesto (2022)
The aquaculture food industry is growing at a fast pace and is about to catch up with fishing in terms of tons produced. However, in Peru aquaculture only represents 1,4 % of the fish industry, with producers who are not very specialized and live in remote areas with lack of technology. For this reason, a semi-autonomous environment monitoring system is being developed exclusively for the eastern zone of Peru, capable of measuring temperature (water and air), dissolved oxygen, pH, and luminosity in real time. For its development, a Parameter Measurement Node is proposed which captures the conditions of the environment and send them to a gateway through the LoRa network. During a 5 days period, more than sixty-nine thousand data points where captured, the system demonstrated that it could measure environmental conditions accurately and autonomously with expected trends for the location and time of measurement. Likewise, it was possible to identify certain correlations between the data, such as ambient temperature and dissolved oxygen, which has a correlation coefficient of 0,81. On the other hand, the use of the LoRa network requires the application of a certain type of information integrity control since it is not provided by default. Finally, it was concluded that the system developed does allow monitoring environmental conditions in the Peruvian rainforest, providing the producer with the ability to visualize his information in real time locally and remotely.